Joni Mitchell archives. Volume 1, The early years, 1963-1967 [compact disc] - Mitchell, Joni (Rhino Records, 2020)
Five CD collection features nearly six hours of unreleased home, live, and radio recordings that flow chronologically to paint a rich portrait of Mitchell's rapid growth as a performer and songwriter during the period leading up to her debut album. This treasure trove of unheard audio includes 29 original Mitchell compositions that have never been released before with her vocals.